Heavily treatment-experienced patients with HIV: are new mechanisms of action enough? - Marisa B. Brizzi; Tracy L. Cable; Dimple C. Patel; Kelli Williams; Zoe Adjei; Carl J. Fichtenbaum (Journal of International Medical Research)
Antiretroviral (ARV) drug resistance poses a threat to ending the HIV epidemic. As the rates of integrase resistance continue to increase globally, the availability of options for HIV treatment becomes limited. Heavily treatment-experienced (HTE) people with HIV (PWH) are limited to two or fewer available fully active ARV classes and are more likely to have an AIDS-defining event. Appropriate identification and management of HTE PWH is crucial to improving patient outcomes and reducing the future spread of drug-resistant HIV. As treatment options become more limited owing to drug resistance, the availability of more potent drugs with a marked increase in virologic suppression is needed in the current ART era. The purpose of this narrative review is to review the identification of HTE PWH, novel mechanisms of resistance, and management of HTE PWH in resource-rich and resource-limited settings using novel ARVs and combination ART.